Pengaruh Kualitas Layanan dalam Membentuk Kepuasan Konsumen di Outlet Minuman Franchise Kota Surabaya - Suddin, Mochammad Muhandis; Febryanto, Indra Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Advances in knowledge and technology today have had a significant impact on global competition. So that the problem is formulated, namely how the influence of the dimensions of service quality on customer satisfaction in the Indonesian Ice Tea franchise industry in Surabaya City and the aim is to find out how the dimensions of service quality taken from the ServQual model affect customer satisfaction. Problem solving uses multiple regression analysis methods to determine some of the effects of service quality dimensions. Data collection uses 70 questionnaires as research data which will be processed using SPSS 27 software. The results obtained after testing show that the variables of reliability, responsiveness, assurance and empathy have an effect on customer satisfaction while the tangibles variable has no effect.